Evaluation of physical education teachers in the leading teacher education program in Dharmasraya regency - Chikitania Larasuria Maronji; Anton Komaini; Damrah Damarah; Zulbahri Zulbahri (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study evaluates the implementation of the Teacher Leadership Program (Program Guru Penggerak/PGP) for Physical Education (PJOK) teachers in Dharmasraya Regency using the CIPP (Context, Input, Process, Product) model. A qualitative descriptive-evaluative approach was employed with eight informants, including teachers, principals, practice instructors, and education office representatives. Data were collected through interviews, observations, and documents, then analyzed using Miles and Huberman’s interactive model with source and method triangulation. Findings indicate that the PGP is relevant to teacher needs and policy, supported by adequate modules and institutional resources, and fosters reflective and collaborative practices. However, technical constraints, time management challenges, and variation in teacher engagement were noted. The program enhances pedagogical competence, instructional leadership, and teacher roles as change agents, though impacts on student outcomes and long-term sustainability require further evaluation.